Finansowanie działań promocyjnych jednostek samorządowych ze środków europejskich - Kańduła, Sławomira (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
A modest of financial resources which self-government units have at their disposal makes in practice well-thought promotion impossible. Joining the European Union by Poland has created possibility to gain external sources to finance promotion activities. The aim of the study is to point at potential abilities of financing promotion campaigns of self-government units from European means. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 60-72